Combination of enteral and parenteral nutrition in the acute phase of critical illness: An updated systematic review and meta‐analysis. Issue 2 (8th June 2021) - Hill, Aileen; Heyland, Daren K.; Ortiz Reyes, Luis A.; Laaf, Elena; Wendt, Sebastian; Elke, Gunnar; Stoppe, Christian
Abstract: Background: Uncertainty remains about the best route and timing of medical nutrition therapy in the acute phase of critical illness. Early combined enteral nutrition (EN) and parenteral nutrition (PN) may represent an attractive option to achieve recommended energy and protein goals in select patient groups. This meta‐analysis aims to update and summarize the current evidence. Methods: This systematic review and meta‐analysis includes randomized controlled trials (RCTs) targeting the effect of EN alone vs a combination of EN with PN in the acute phase of critical illness in adult patients. Assessed outcomes include mortality, intensive care unit (ICU) and hospital length of stay (LOS), ventilation days, infectious complications, physical recovery, and quality‐of‐life outcomes. Results: Twelve RCTs with 5543 patients were included. Treatment with a combination of EN with PN led to increased delivery of macronutrients. No statistically significant effect of a combination of EN with PN vs EN alone on any of the parameters was observed: mortality (risk ratio = 1.0; 95% CI, 0.79–1.28; P  = .99), hospital LOS (mean difference, −1.44; CI,  −5.59 to 2.71; P = .50), ICU LOS, and ventilation days. Trends toward improved physical outcomes were observed in two of four trials. Conclusion: A combination of EN with PN improved nutrition intake in the acute phase of critical illness in adults and was not inferior regarding the patients' outcomes. Large, adequately designed trials in select patient groups are needed to answer the question of whether this nutrition strategy has a clinically relevant treatment effect.